2001
DOI: 10.1023/a:1017919305501
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Three-hundred and eight outpatient elderly subjects (> or = 65 years) were randomly assigned to receive the MF59-adjuvanted influenza vaccine (FLU-AD; n = 204) or a conventional subunit influenza vaccine (AGRIPPAL S1; n = 104) in order to compare the safety and immunogenicity of the two vaccines. Although mild pain at the injection site was reported more frequently by subjects immunised with the adjuvanted vaccine, both vaccines were shown to be safe and well tolerated. The adjuvanted vaccine was more immunoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(22 citation statements)
references
References 29 publications
3
18
0
1
Order By: Relevance
“…One of the proposed mechanisms of action of the MF59-adjuvanted influenza vaccine is production of a local immunostimulatory environment at the injection site by promotion of immune mediators in muscle fibers. Indeed, the MF59-adjuvanted influenza vaccine has been shown to enhance the immune response and offer increased clinical protection in the elderly over that offered by the conventional subunit vaccine (17,23,24). Consistent with these studies, we also observed superior immunogenicity conferred by the MF59-adjuvanted vaccine over that by the conventional subunit vaccine (24,25).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…One of the proposed mechanisms of action of the MF59-adjuvanted influenza vaccine is production of a local immunostimulatory environment at the injection site by promotion of immune mediators in muscle fibers. Indeed, the MF59-adjuvanted influenza vaccine has been shown to enhance the immune response and offer increased clinical protection in the elderly over that offered by the conventional subunit vaccine (17,23,24). Consistent with these studies, we also observed superior immunogenicity conferred by the MF59-adjuvanted vaccine over that by the conventional subunit vaccine (24,25).…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, the MF59-adjuvanted influenza vaccine has been shown to enhance the immune response and offer increased clinical protection in the elderly over that offered by the conventional subunit vaccine (17,23,24). Consistent with these studies, we also observed superior immunogenicity conferred by the MF59-adjuvanted vaccine over that by the conventional subunit vaccine (24,25). To the best of our knowledge, this is one of the very few studies comparing the immunogenicity of the intradermal vaccine with that of the MF59-adjuvanted vaccine (11,14).…”
Section: Discussionmentioning
confidence: 99%
“…We identified 60 eligible articles published between 1987 and 2006 describing inactivated seasonal influenza vaccine immunogenicity studies conducted in the United States, Canada, Europe, Israel, and Russia 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 . We included 129 independent study arms of which 119 reported data on response to A/H1N1, 109 on influenza B, and 108 on A/H3N2 vaccine strains (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…An adjuvanted form of TIV that contains inactivated, viral antigens combined with the oil in water emulsion adjuvant MF59 98 has been licensed in Europe since 1997 and is used in 26 countries in the elderly (.65 y old) on the basis of improved immune responses in this risk group. 99,100 More than 40 million adults have received the vaccine and post-licensure studies indicate an acceptable safety profile. In 2010, a high-dose preparation of TIV was licensed in the United States for use in the elderly.…”
Section: Correlates For New Influenza Vaccine Approaches Within Specimentioning
confidence: 99%